Optimum Post-Warranty Maintenance Policies for Products with Random Working Cycles - Yongjun Du; Lijun Shang; Qingan Qiu; Li Yang (Mathematics, 2022)
The working cycle of the products can be supervised by sensors and other measuring technologies. This fact means that by supervising the working cycle, the manufacturer can devise a warranty policy, and by continuing to supervise the post-warranty working cycle, the consumer can model the post-warranty maintenance. However, in the literature, there is no associated work. Integrating a renewing free-replacement warranty (RFRW) and the number of working cycles, this paper proposes a two-dimensional renewing free-replacement warranty policy, which can be applied to warrant the product and analyze the related warranty cost. By extending the warranty policy to the post-warranty maintenance model, we investigate two kinds of post-warranty maintenance models, including the uniform post-warranty maintenance model and the customized post-warranty maintenance model. For each post-warranty maintenance model, we provide an algorithm to seek the optimum solution. Finally, we provide some numerical experiments to demonstrate the model. The numerical results show that for the produced warranty cost, the traditional RFRW is higher than the proposed warranty policy, and the customized policy is inferior to the uniform policy.